Transoral transvsetibular thyroidectomy: an initial approach and experience - Mehta, Raghav; Jain, Sanchit; Soni, Ravindra (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The objective of the study was to record our intial experience of transoral transvestibular thyroidectomy and to ascertain the problems faced, their possible solutions and further suggestions. Methods: Inclusion criteria were unilateral thyroid swelling, patients who had a neck ultrasound (US) with a estimated thyroid diameter not larger than 8 cm; (b), USG estimated gland volume ≤40 ml, nodule size ≤50 mm, A benign tumor, such as a thyroid cyst, single-nodular goitre, or multinodular goitre. The procedure is carried out through a three-port technique placed at the oral vestibule, one 10-mm port for 30° endoscope and two 5-mm ports for dissecting and coagulating instruments. CO2 insufflation pressure is set at 6 mmHg. An anterior cervical subplatysmal space is created from the oral vestibule down to the sternal notch, laterally to the sternocleidomastoid muscle. Thyroidectomy is done fully endoscopically using conventional endoscopic instruments and Harmonic. Results: All transoral transvestibular thyroidectomy procedures were performed successfully with no conversions. The mean operative time was 112.5 (90-180) min. We observed one case of transient postoperative hypocalcemia. There was no recurrent laryngeal nerve palsy. The cosmetic result was excellent in all patients. Conclusions: Transoral transvestibular thyroidectomy may provide a method for ideal cosmetic results. It also provides a wide and enhanced endoscopic view. Though more study and further instrumental development is required to fully embrace this procedure a preliminary experience show encouraging results.